Goats locomotion energy expenditure under range grazing conditions: Seasonal variation - Lachica, M; Somlo, R; Barroso, F G; Boza, J; Prieto, C (JOURNAL OF RANGE MANAGEMENT, 1999)
The estimation of the energy cost of various activities using calorimetric techniques in conjunction with direct field observations can be used to estimate energy expended in the daily activities of free-ranging animals. The objective of this study was to observe and quantify the grazing activities and to estimate the energy expenditure due to locomotion of goats in open range. The study was carried out at `Finca de Bonaya' privately-owned site, which extends over 1,482 ha, located in the Nevada mountain-range, Almeria. The local altitude varies from 1,100 to 2,000 m above sea level. The area has a mediterranean mountain climate, with annual precipitation ranging from 400 to 700 mm and average daily temperatures from 4.7 degrees C in winter to 23.0 degrees C in slimmer. Landscape is characterised by holm oak wood and pine wood, degradation scrubs and hydrophilic grasses communities. The experimental flock grazed on 3 routes during the whole year. The goats were released to graze during the day and then returned to an enclosed shed. The type of goat management was considered as semi-extensive. Direct observation was used to simulate the total distance walked, the vertical ascent or descent, and to quantify other grazing activities. Data on activities on range and distance travelled were taken on 3 days in each season. The energy expenditure of locomotion was calculated from the horizontal and vertical components of travel and the corresponding costs, which had been previously obtained by calorimetry. There was no significant seasonal effect on period devoted to specific activities on range (P>0.05). However, significant changes in the estimated daily energy expenditure and extra energy expenditure due to locomotion of the animals at pasture were found in different seasons (P<0.05). Grazing and walking were the primary activities of goats throughout the study, accounting for 51.7 and 42.0% of the animals' daily period on range, respectively. Daily travelled distances by goats on range fluctuated from 12,777 m in summer to 8,100 m in autumn, with an annual average of 9,954 m, which represents a mean speed of 20.8 m/min calculated over the whole period on range. The mean annual vertical ascent or descent was 500 m. Estimated heat production due to locomotion ranged from 130.9 to 88.5 kJ/kg(0.75) per day in summer and autumn respectively. These values account for an increased metabolizable energy (ME) requirement at pasture above maintenance of 46.6 and 31.6%, respectively, assuming a ME requirement for maintenance of 401 kJ/kg(0.75) per day for the restrained goat.
Keywords: Goats; Grazing; heat production; locomotion